(untitled) (Eurasian Journal of Philology Science and Education, 2018)
This article is devoted to the problem of translation of literary texts with high ethno-cultural identity. When translating such texts from one language to another, not only different language systems are compared, but also different cultures. The article highlights the difficulties and mistakes made by translators in the translation process. The article discusses the poem of Abay, which is full of lexical units with ethno-cultural component and A. Nurpeisov’s trilogy Blood and sweat.